2012
DOI: 10.1210/en.2011-1102
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogonia Differentiation Requires Retinoic Acid Receptor γ

Abstract: Vitamin A is instrumental to mammalian reproduction. Its metabolite, retinoic acid (RA), acts in a hormone-like manner through binding to and activating three nuclear receptor isotypes, RA receptor (RAR)α (RARA), RARβ, and RARγ (RARG). Here, we show that 1) RARG is expressed by A aligned (A(al)) spermatogonia, as well as during the transition from A(al) to A(1) spermatogonia, which is known to require RA; and 2) ablation of Rarg, either in the whole mouse or specifically in spermatogonia, does not affect meios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
118
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 47 publications
15
118
2
Order By: Relevance
“…1 K-N; Fig. S1), which are markers of Aal spermatogonia (10,21). In contrast, KIT, which is expressed in A1 to B spermatogonia, was never detected in the seminiferous tubules of Aldh1a1-3 Ser−/− mutants ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…1 K-N; Fig. S1), which are markers of Aal spermatogonia (10,21). In contrast, KIT, which is expressed in A1 to B spermatogonia, was never detected in the seminiferous tubules of Aldh1a1-3 Ser−/− mutants ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…We and others have demonstrated that testicular RA mainly originates from Sertoli cells especially in puberty; however, it remains elusive whether the action of RA on spermatogonial differentiation is through germ cells or Sertoli cells, or both Sertoli and germ cells, as its receptors, RARs and RXRs, are expressed in both Sertoli cells and the undifferentiated spermatogonia (Gely-Pernot et al, 2012;Tong et al, 2013;Vernet et al, 2006b;Gaemers et al, 1998;DeFalco et al, 2015). For instance, genetic ablation of Rarg in germ cells resulted in only mild spermatogonial differentiation defects in mutants younger than one year old, indicating that either retinoid signaling in Sertoli cells is involved in spermatogonial differentiation, or that other subtypes of RARs in spermatogonia compensate for loss of RARγ function, as it is the case for many other developmental process (Gely-Pernot et al, 2012;Mark et al, 2009). Thus, to better understand whether the modulation of spermatogonial differentiation by retinoid signaling occurs directly via the germ cells, it is necessary to completely inactivate retinoid signaling, specifically in germ cells.…”
Section: Discussion Retinoid Signaling Directly Controls Spermatogonimentioning
confidence: 99%
“…Global inactivation of individual RAR genes such as Rara results in male sterility and aberrant spermatogenesis (Lufkin et al, 1993). Several lines of compound mutants lacking multiple RARs or RXRs have been studied in testis, suggesting that retinoid signaling plays a crucial role in spermatogonial differentiation (Gely-Pernot et al, 2012. However, the RA target genes implicated in spermatogonial differentiation need to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…When VAD animals are injected with RA or vitamin A, the arrested spermatogonia differentiate (17)(18)(19), and the arrested preleptotene spermatocytes initiate meiosis (18). During spermatogonial differentiation, RA is believed to act, at least in part, directly on germ cells: Spermatogonia express RA receptors (RARs) (20), and genetic ablation of RARs in germ cells modestly impairs spermatogonial differentiation (21).…”
Section: Significancementioning
confidence: 99%